Prognostic impact of anemia according to frailty status in elderly patients with acute coronary syndromes. Issue 1 (January 2020) - Ariza-Solé, Albert; Lorente, Victòria; Formiga, Francesc; López-Palop, Ramon; Sanchís, Juan; Marín, Francisco; Vidán, María T.; Martínez-Sellés, Manuel; Sánchez-Salado, José C.; Garay, Alberto; Guerrero, Carme; Bueno, Héctor; et al.
Abstract : Aims: Anemia is associated with poorer outcomes in patients with acute coronary syndromes (ACS), but the magnitude of this association in elderly patients remains poorly understood. No study has assessed the prognostic impact of anemia according to frailty status in this setting. Methods: The LONGEVO-SCA registry included unselected ACS patients aged at least 80 years. A geriatric assessment was performed during hospitalization, including frailty assessment using the FRAIL scale. Anemia was defined by the WHO criteria. We evaluated the impact of anemia on 6-month mortality according to the presence of frailty. Results: A total of 517 patients were assessed. Mean age was 84.3 years, and a total of 236 patients (45.6%) had anemia. Patients with anemia had a higher prevalence of comorbidities and higher prevalence of frailty (30.6 vs. 22.3%, P  = 0.007). A total of 60 patients (12.1%) died at 6 months [40 with anemia (17.5%) and 20 without anemia (7.5%), P  = 0.001]. Anemia was independently associated with mortality at 6 months in the whole cohort (hazard ratio 2.28, 95% CI 1.13–457, P  = 0.021). The association of anemia and mortality was different according to frailty status, being significant in patients without frailty (hazard ratio 3.94, 95% CI 1.84–8.45, P  = 0.001), but not in frail patients (hazard ratio 1.17, 95% CI 0.53–2.57, P  = 0.705), ( P value for interaction = 0.035). Conclusion: A high proportion of elderly patients with ACS have anemia, leading to a worse prognosis in the whole cohort. The association between anemia and mortality was especially significant in robust patients, whereas the poorer prognosis in frail patients was not modified by the presence of anemia.